2004
DOI: 10.1093/ajcn/79.6.1020
|View full text |Cite
|
Sign up to set email alerts
|

Combining wheat bran with resistant starch has more beneficial effects on fecal indexes than does wheat bran alone

Abstract: Combining WB with RS had more benefits than did WB alone. This finding may have important implications for the dietary modulation of luminal contents, especially in the distal colon (the most common site of tumor formation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 34 publications
8
99
0
2
Order By: Relevance
“…With healthy young subjects on a typical Western diet the gastrointestinal transit time has generally been o3 days (Wyman et al, 1976;Stasse-Wolthuis et al, 1980;Eastwood et al, 1986;Haack et al, 1998) or o2 days (Muir et al, 2004). In the present study, the detected transit times were very short (38714 h) and the defecation frequency high (1.070.4 times per day).…”
Section: Fecal Lipid Content and Compositionsupporting
confidence: 40%
“…With healthy young subjects on a typical Western diet the gastrointestinal transit time has generally been o3 days (Wyman et al, 1976;Stasse-Wolthuis et al, 1980;Eastwood et al, 1986;Haack et al, 1998) or o2 days (Muir et al, 2004). In the present study, the detected transit times were very short (38714 h) and the defecation frequency high (1.070.4 times per day).…”
Section: Fecal Lipid Content and Compositionsupporting
confidence: 40%
“…Twelve randomised controlled trials were identified that presented evidence on wheat fibre in relation to intestinal transit time (Connell & Smith, 1974;Jenkins et al, 1975;Cummings et al, 1976;Wyman et al, 1976;Stasse-Wolthuis et al, 1980;Andersson et al, 1983;Spiller et al, 1986;Stevens et al, 1988;Tomlin & Read, 1988;Vuksan et al, 1999;Muir et al, 2004;Vuksan et al, 2008) (Colo-rectal health review, p 34-41, 43).…”
Section: 94mentioning
confidence: 99%
“…Ten randomised controlled trials were identified that presented evidence on resistant starch supplementation in relation to faecal weight, of which seven were included in a meta-analysis (Phillips et al, 1995;Cummings et al, 1996;Silvester et al, 1997;Heijnen et al, 1998;Jenkins et al, 1998;Behall et al, 2002;Muir et al, 2004). There was no indication that doses of 12g/day or less had any effect on faecal wet weight, so only data from doses greater than 12g/day were used.…”
Section: Faecal Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing small intestinal digesta viscosity increases rate of passage through the intestine (Bueno and Fioramonti 1994) thereby decreasing the opportunity for digestion and absorption of nutrients (Ellis et al 1996) and leading to passage of fermentable products to the colon. The accumulation of the products of fermentation in the colon can restrict water re-absorption leading to increased frequency of more moist stools (Muir et al 2004). Increasing dietary barley or corn proportions from 20 to 80% of diet DM increased viscosity of duodenal digesta supernatant by 35 and 48%, respectively (Mir et al 2000), with the viscosity ranges in steers fed corn being greater than of those fed barley.…”
Section: Measurement Of Digesta Viscosity and Its Interaction With Thmentioning
confidence: 99%